Natural Capital and the Resource Curse - Canuto, Otaviano; Cavallari, Matheus (World Bank, Washington, DC, 2012)
An abundance of natural resources is intuitively expected to be a blessing. Nonetheless, it has been argued for some decades that large endowments of natural resources oil, gas, and minerals in particular may actually become more of a curse, often leading to slow economic growth and redistributive struggles (including armed conflict). Over the years, vast empirical literature has addressed this "paradox." The literature has had to rely on proxies for natural resource abundance because of the lack of appropriate data, generating doubt on whether results would be similar if direct measures of natural wealth were available. This gap is now starting to be filled with the data series released by the World Bank (1997, 2006, 2011) on natural capital and other forms of countries' wealth. This note presents an analysis of these data to revisit some of the conclusions reached in the literature on the relationship between natural resource abundance and economic growth. The findings are in alignment with the view that there is no clear deterministic evidence of natural resource abundance as a curse or a blessing; therefore, the effect on a country depends on other determinants.